Teacher Leadership and Educational Reforms in UAE (Global Journal of Management and Business Research, 2012)
This paper is an attempt to highlight operational deficiencies in the execution of educational reforms in UAE with relation to academic leadership. However, this study concluded that UAE is not ready for the change of this magnitude because of its rigid culture.
Keywords: highlight operational deficiencies